Finite Element Analysis on Dissimilar Thickness Joining of The Tailor-Welded Blank Process - Mohd Zaidi, Sidek; Anas Basri, Musthafa; Jasri, Mohamad; Muhamad Rozikin, Kamaluddin (2013)
Tailor welded blanks are defined as a joining process for two or more pieces of flat material with dissimilar material types or thickness, and or mechanical properties. TWBs in automotive parts manufacturing will increase with the improvement in welding technology and development of newer light materials available (Das, 2000). Tailored blanks are usually produced by laser welding and it is not possible to use standard tests to determine mechanical properties of the weld zone in tailor-welded blanks (Rojek et al., 2012). As heat is main contribution factor, it is important to determine correct positioning of the heating in setting up the TWB process; it must be balanced and optimized. In this study, the finite element analysis has been adopted to determine optimum heating arrangement for joining the different aluminum thickness.